Augmented Reality Dalam Visualisasi Katalog Penjualan Toko Aneka Furniture Berbasis Android Menggunakan Algoritma Fast Corner Detection - Krisna Syahira Wibowo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The furniture business has the promised chance of success. This is because this business has a high enough purchasing power and needs. So it takes innovation in attracting the purchasing power of consumers. Promotion is one of the most important factors in running a business. Currently, the promotion process for furniture stores uses a lot of sales catalogs. Therefore, innovation is needed in promoting commercial goods to be marketed. Due to the development of technology, it is proposed to apply a strategy using augmented reality technology which is implemented into an android-based application with a marker based tracking method and uses several algorithms to compare, namely the Fast Corner Detection algorithm. With markers that are run through the android application and each marker contains an image of the furniture to be detected. Once detected, a 3-dimensional object will appear above the marker. In addition, the details of the furniture will look more alive and real. That way, it is expected to provide innovation and attraction for customers who will buy. This research produces an android application as a promotional tool in the marketing of the Aneka Furniture Store products to make it more interactive. AR implementation using the FAST Corner Detection algorithm is very helpful in detailing a product that will be marketed by the company through 3D objects to attract more buying interest from Aneka Furniture Store consumers.